Treatment recommendations for chronic knee osteoarthritis. Issue 3 (September 2020) - Gress, Kyle; Charipova, Karina; An, Daniel; Hasoon, Jamal; Kaye, Alan D.; Paladini, Antonella; Varrassi, Giustino; Viswanath, Omar; Abd-Elsayed, Alaa; Urits, Ivan
Abstract : Primary osteoarthritis (OA) hinders an aging global population as one of the leading causes of years-lost-to-disability (YLD). OA in most patients is considered to be an overuse injury that results in degenerative inflammation of the joints with the associated formation of bony outgrowths. Due to the escalating nature of this chronic pain disease, treatment management for OA can initially begin with a more conservative approach. It can eventually lead to more invasive surgical procedures. At present, the standard of care remains initial conservative management with lifestyle changes, including weight loss with concurrent anti-inflammatory regimens. Injections are frequently used for the escalation of care, but a significant number of patients ultimately resort to total knee arthroplasty. This review will focus specifically on knee OA, providing a brief overview of risk factors and early management and in-depth exploration of the invasive interventions that can offer symptomatic relief and return of function.